2015
DOI: 10.1136/bcr-2015-210239
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release oral morphine as an alternative to methadone for the treatment of opioid-use disorder post Torsades de Pointes cardiac arrest

Abstract: SUMMARY In most settings, approved medications for the treatment of opioid-use disorder include methadone and buprenorphine/naloxone, and in some settings, naltrexone. We present a case in which methadone administration was associated with an in-hospital episode of Torsades de Pointes in a patient who was subsequently maintained on sustained release oral morphine (SROM) for treatment of his opioid-use disorder. This transition was made in the context of long-term compliance to methadone maintenance, and with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Dose reduction or substitution of methadone is also reasonable. Some alternatives of methadone may also be considered including buprenorphine, naltrexone, or slow releasing morphine [ 11 ]. For patients with ventricular tachyarrhythmia, in addition to cessation of offending agents and electrolyte correction, magnesium sulfate is the first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Dose reduction or substitution of methadone is also reasonable. Some alternatives of methadone may also be considered including buprenorphine, naltrexone, or slow releasing morphine [ 11 ]. For patients with ventricular tachyarrhythmia, in addition to cessation of offending agents and electrolyte correction, magnesium sulfate is the first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in the slow-release oral morphine (SROM), as a potential effective candidate for maintenance treatment [90][91][92]. This medication is given once daily, and it suits those individuals who cannot tolerate methadone, respond poorly to other available treatments, or show a prolonged QT [93][94][95]. However, the last Cochrane meta-analysis reported that there is not enough evidence to confirm the effectiveness of SROM for opioid maintenance, as only three inconclusive studies exist [96].…”
Section: Drugs Acting On Opioid Receptorsmentioning
confidence: 99%
“… 7 Morphine has been considered low risk from the perspective of QT interval prolongation 15 and has been suggested for treating opioid addicts who have a prolonged QT interval. 24 However, opium is a mixture of several substances with different effects that may ensue the different clinical manifestations. 9 Yet, there is no evidence that opium consumption is associated with the higher prevalence of prolonged QT interval compared to non-user general population.…”
Section: Introductionmentioning
confidence: 99%